In vitrocalculus detection with a moved smart ultrasonic device - Grit Meissner (Blackwell Synergy, 2006)
Study objective: The objective of subgingival instrumentation of periodontally diseased root surfaces is to remove the adhering microbial biofilm and calcified deposits. Recently, we have described an automated calculus detection system under static conditions. Clinically however, the tip of the system has to be moved over tooth surfaces. It was thus necessary to study the entire system in motion. Methods: The detection device is based on a conventional dental piezoelectric ultrasonic handpiece with a conventional scaler insert. The impulse response of the mechanical oscillation system is analysed by a fuzzy logic-based computerized algorithm, which classifies various surfaces. The present study investigates dental surface recognition properties of the new system with the tip being moved over teeth surfaces in vitro. Following a training set of 7977 measurements (3960 calculus, 4017 cement) on 200 extracted teeth, 1363 measurements were conducted on 34 teeth unknown to the system. Results: The surfaces cementum and calculus were correctly classified in 78% within the training set and in 81% within the set unknown, with a k value of 0.68. Conclusion: It was shown that this method of automatic recognition of tooth surfaces is able to distinguish between different tooth surfaces in vitro independently from tip movements.